SPIRITUALITAS GURU AGAMA KATOLIK BERDASARKAN GRAVISSIMUM EDUCATIONIS - Herman Lias; Agustinus Wisnu Dewantara (Bahasa Indonesia, 2022)
The essence of spirituality in the professional appreciation of Catholic religious teachers as the basis for a complete life renewal. Gravissimum Educationis is the truth of the theory used in this research. The research method uses a qualitative approach, namely literature study. This study aims to find new concepts and theories about the spirituality of Catholic religious teachers. Spirituality is awareness and belief in faith which is the basis of encouragement in life renewal. Self-awareness as a Catholic religion teacher is lived in faith, that his calling in life is a call that comes from Jesus Christ himself. Spirituality needs to be realized in living up to the life vocation of a Catholic religious teacher as a professional. A professional Catholic religious teacher means having a deep spirituality. Deep spirituality makes Catholic religious teachers more leverage in optimizing their competencies, namely competence as professional educators and at the same time as preachers of the Word of God. Catholic religious teachers who have deep spirituality are able to present the whole, both in their duties and in daily life.